Nausea, Vomiting of Pregnancy and P6 Acupressure - Goudia, Amel Dawod Kamel; Toukhi, Noura Mohamed El; PH, Livana; Ghadeer, Hend Al (GLOBAL HEALTH SCIENCE GROUP, 2023)
Nausea and vomiting of pregnancy (NVP) has been recognized as a feature of early pregnancy for well over 2000 years. Pregnancy is a unique period of life for most women. Multiple hormonal, physiological, and biomechanical changes, such as increased blood volume and heart rate, weight gain and shift in the center of mass, proceed normally in almost all pregnant women. Nausea and vomiting is a physically morbid disease, it’s severity significantly impacts pregnant woman life and her pregnancy experience, specially the quality of life and work function during early pregnancy.